Transforming lives and empowering communities: evidence, harm reduction and a holistic approach to people who use drugs. Issue 5 (September 2019) - Southwell, Mat; Shelly, Shaun; MacDonald, Virginia; Verster, Annette; Maher, Lisa
Abstract : Purpose of review: We reviewed the global state of harm reduction for people who use and/or inject drugs. Key findings: Although harm reduction is now the key response to HIV among people who use drugs globally, intervention coverage remains suboptimal, exacerbated by chronic under-funding, declining donor support and limited domestic investment, particularly in low-income and middle-income countries. We describe the current environment and review recent innovations and responses, including peer distribution of naloxone, low dead space syringes, drug consumption rooms and drug-checking services. However, despite efforts by people who use drugs and supporting partners to sustain harm reduction services and to develop and implement novel interventions, programmes are often under-scaled and under-resourced and people who use drugs continue to face significant barriers to accessing services. Summary: There is an urgent need to bring existing harm reduction programmes to scale and to broaden their scope, as well to complement them with innovative interventions targeting new populations and new substances. Under and disinvestment in harm reduction and the absence of enabling legal environments threatens to undermine the global HIV response and exacerbate the morbidity and mortality associated with the current epidemic of opioid overdose.